Effect of labor division between wife and husband on the risk of divorce: evidence from German data - Kornelius Kraft; Stefanie Neimann (Institute for the Study of Labor (IZA), 2009)
Using German panel data from 1984 to 2007, we analyze the impact of labor division between husband and wife on the risk of divorce. Gary Becker's theory of marriage predicts that specialization in domestic and market work, respectively, reduces the risk of separation. Traditionally, the breadwinner role is assigned to the husband, however, female labor force participation and their wages have risen substantially. Our results suggest that there are gender-specific differences, e.g. female breadwinner-couples have a substantially higher risk of divorce than male breadwinner-couples. In contrast, the equal division does not significantly alter the probability of separation.
urn:nbn:de:101:1-20091105860
Keywords: J12; J22; 330; Divorce; labor division; Germany; Scheidung; Familienökonomik; Geschlecht; Frauenerwerbstätigkeit; Deutschland